2011
DOI: 10.1126/science.1200172
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Visual Pigments by Light and Heat

Abstract: Vision begins with photoisomerization of visual pigments. Thermal energy can complement photon energy to drive photoisomerization, but it also triggers spontaneous pigment activation as noise that interferes with light detection. For half a century, the mechanism underlying this dark noise has remained controversial. We report here a quantitative relation between a pigment’s photoactivation energy and its peak-absorption wavelength, λmax. Using this relation and assuming that pigment activations by light and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
178
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(189 citation statements)
references
References 35 publications
8
178
2
1
Order By: Relevance
“…The common PSB11 chromophore of melanopsins and rhodopsins does not guarantee that the same mechanism operates in both photoreceptors. This not only concerns light-induced activation but also thermal activation: a process whose rate limits the photoreceptor light sensitivity and that is currently associated with thermal, rather than photochemical, PSB11 isomerization (19)(20)(21)(22)(23)(24).…”
Section: Significancementioning
confidence: 99%
“…The common PSB11 chromophore of melanopsins and rhodopsins does not guarantee that the same mechanism operates in both photoreceptors. This not only concerns light-induced activation but also thermal activation: a process whose rate limits the photoreceptor light sensitivity and that is currently associated with thermal, rather than photochemical, PSB11 isomerization (19)(20)(21)(22)(23)(24).…”
Section: Significancementioning
confidence: 99%
“…Rhodopsins with absorption at the red edge of the spectrum (XL-iodopsins) are found in flies, mollusks, fish, and in some birds. At this spectral range, thermal isomerization increases, producing significant background at high rhodopsin concentrations (3). On the other end of the spectrum, the UVAabsorbing pigment is of limited use because UV-transparent lenses promote damage of the retina.…”
mentioning
confidence: 99%
“…Therefore, the incident light must propagate through five reflecting and scattering layers of cell bodies and neural processes before reaching the photoreceptors. This 'inverted' retinal structure is expected to cause blurring of the image and reduction in the photon flux reaching the photoreceptors, thus reducing their sensitivity [6][7][8][9] . It has been recently reported that retinal Müller cells act as light guides serving to transfer light across the retina, from the vitreo-retinal border towards the photoreceptors [10][11][12] .…”
mentioning
confidence: 99%